How It All started and How It Evolved: Ray’s Whip - Nicoletta Stame (Journal of MultiDisciplinary Evaluation)
Background: The chapter reconstructs the origin of the concept of “streams of evidence” in the collective work of the Inteval group, as proposed in the book From Studies to Streams (Rist, Stame, 2006). Contrary to insisting on the (scarce) utilization of single studies, answering the evaluation demands of static organizations, based on their “own incentives and reward structures”, Ray challenged the group to engage with the new scenario of the learning organizations “that embraced learning and knowledge as fundamental to their own existence and success”. Such organizations needed evaluative knowledge that was “timely, proactive and drawing on multiple sources of knowledge”, that could be provided by different sources, evaluations and research, internal or external to the organizations.